2009
DOI: 10.1007/s10592-009-0030-y
|View full text |Cite
|
Sign up to set email alerts
|

Trait specific consequences of fast and slow inbreeding: lessons from captive populations of Drosophila melanogaster

Abstract: The increased homozygosity due to inbreeding leads to expression of deleterious recessive alleles, which may cause inbreeding depression in small populations. The severity of inbreeding depression has been suggested to depend on the rate of inbreeding, with slower inbreeding being more effective in purging deleterious alleles of smaller effect. The effectiveness of purging is however dependent on various factors such as the effect of the deleterious, recessive alleles, the genetic background of inbreeding depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 45 publications
5
30
0
Order By: Relevance
“…Males in the PT population had an especially short lifespan (Table 3), which can be related to their high RMR (73,74), although we realize that association between RMR and lifespan is still under debate (75). Studies examining the effect of increased homozygosity (inbreeding) on metabolic rate are scarce (76)(77)(78). A study on the cricket Gryllodes sigillatus (only males) found an 80% increase in RMR of inbred crickets over that in outcrossed individuals, along with a slight decrease in metabolic rate during forced exercise (79).…”
Section: Discussionmentioning
confidence: 99%
“…Males in the PT population had an especially short lifespan (Table 3), which can be related to their high RMR (73,74), although we realize that association between RMR and lifespan is still under debate (75). Studies examining the effect of increased homozygosity (inbreeding) on metabolic rate are scarce (76)(77)(78). A study on the cricket Gryllodes sigillatus (only males) found an 80% increase in RMR of inbred crickets over that in outcrossed individuals, along with a slight decrease in metabolic rate during forced exercise (79).…”
Section: Discussionmentioning
confidence: 99%
“…Swindell and Bouzat 2006a;Vermeulen et al 2008;Bilde et al 2009). Lifespan is assumed to be extremely sensitive to a large number of environmental factors and it is therefore considered a suitable trait for studies investigating the effects that environmental factors can exert on the level of inbreeding depression (Vermeulen and Bijlsma 2004 and generally low levels of inbreeding depression on resistance to heat, cold and desiccation stresses have also been reported in D. melanogaster (Mikkelsen et al 2010). Studies investigating the effects of inbreeding on survival under starvation appear less numerous.…”
Section: Effects Of Inbreeding Are Trait Specificmentioning
confidence: 99%
“…Whether good quality individuals have higher or lower rate of metabolism is however still an unresolved question (Hawkins and Day 1999;Konarzewski and Diamond 1995;Reinhold 1999;Nilsson 2002;Rantala and Roff 2006;Johnston et al 2007;Ketola and Kotiaho 2009a, b;Mikkelsen et al 2010). The environment in which a population has evolved to live may have fundamental effects on its metabolic strategy in the sense that a low metabolic rate is favored in areas where food supply is scarce, while high metabolic rate is favored in areas where food supplies are abundant (Mueller and Diamond 2001).…”
Section: Inbreeding Affects Metabolic Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…In modern human-transformed landscapes, the populations of many species are under various pressures including habitat loss and degradation, resulting in increasingly small and isolated populations (Mikkelsen et al, 2010). Small population size, in turn, increases the risk of genetic erosion through drift and inbreeding (Hoffmann and Hercus, 2000).…”
Section: Introductionmentioning
confidence: 99%